Empowering Women-Owned MSMEs in Makassar City through Digital Technology Support - Darmayanti, Resty Rahayu; Wahira, Wahira (Pinisi Journal of Social Science, 2025)
MSMEs are one of the pillars of the economy in Makassar City, especially small and home-based businesses that are mostly run by women. The development of digital technology has created new opportunities for women to manage their businesses more flexibly and expand their market reach without neglecting their roles at home. This study aims to understand how digital technology can support the empowerment of women MSMEs in Makassar City, while identifying the obstacles they face in the transformation process. The research uses a qualitative approach through a literature review that includes scientific articles, policy reports, and other supporting documents relevant to the topic of digitalization of women's MSMEs. The analysis was conducted by tracing findings that have a correlation between the use of technology and increased business capacity. The results of the study show that digitization provides benefits in the form of improved marketing skills, expanded sales networks, innovation in products and services, and increased confidence among women as business actors. Empowerment is not only evident from an economic perspective, but also from women's ability to make independent business decisions. Conditions in the field show that there are still many challenges that need to be addressed, such as low digital and financial literacy, limited capital, uneven internet access, and domestic burdens that take up women's time in learning technology. Sustainable change requires strong ecosystem support through consistent training, business mentoring, collaboration among stakeholders, and access to financing that is friendly to women's MSMEs. This study provides a basis for designing more effective digital empowerment strategies and opens up space for further research focusing on the real experiences of women MSME entrepreneurs in Makassar.